ARCHITECTURAL MONUMENTS ESTABLISHED DURING THE PERIOD OF AMIR TEMUR AND TEMURIS IN SAMARKAND, THE PEARL OF THE GREAT SILK ROAD (World Bulletin of Management and Law, 2023)
This article is about the analysis of the constructions built during the era of Sahibqiron Amir Temur and his successors, the authors who witnessed their construction process and the researchers who studied the historical monuments of the Timurid period in the following periods, opinions and comments.